THE IMPACT OF DEMOGRAPHY AND PERCEPTION ON MALE CONTRACEPTIVE USE IN INDONESIA: Contraceptive Use - Amraeni, Yunita; Kamso, Sudijanto (Universitas Mandala Waluya Kendari, 2020)
Background: Increasing men's empowerment in family planning and reproductive health is needed, One of the ways is understanding of factors encourage husbands to a family planning acceptor. This study aims to determine the relationship between knowledge, education and husband's perceptions of family planning with the participation of husbands as family planning acceptors in Indonesia. Methods: A cross sectional study design was applied in this study using the 2017 IDHS basic data with 3,751 respondents. Qualitative study on 20 husband with indepth interview also was done toexploretheir perception aboutcontraception. The study used univariable and bivariable analysis with Chi-square test. Results: The results showed that husband's knowledge, education and perceptions about family planning had a significant relationship with each p-value = 0,000 smaller than ? = 0.05. Most of husbandsarguedthat men should not be involved in family planning because it is related to culture and fear of side effects. Conclusion: The low percentage of husband's participation in family planning shows that husband should be encouraged to participate into family planning program.